Case Study - Not to be Missed: Scrotal Gangrene - Iqbal, Nadeem (International Journal For Research In Health Sciences And Nursing, 2019)
SCROTAL GANGRENE ,also known as Fournier's gangrene is a rare but life threatening disease. Constellation of clinical features along with developing sepsis includes genital pain and tender scrotum with skin swelling and genital skin showing ecchymosis, blistering or epidermolysis of skin . But worth noticing is Worsening pain which out of proportion to the visible signs. Requires early diagnosis and prompt surgical referal so have better prognosis.If untreted may result in serious consequences.So not to be missed .